ADAPTING OF THE MILITARY PHARMACEUTISTS TO LABOUR ACTIVITY - N. I. Khomutetskaya; A. G. Golub (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article is devoted to problems of the military pharmaceutists labour adapting. The probable approaches of problem solution of preparation of the students to next independent activity are considered.